Implementation of a specialized neuroprognostication consultation program and associated provider attitudes: A survey-based study - David Fischer; Sahily Reyes-Esteves; Connor Law; Alice Ford; Peter Schwab; Benjamin S. Abella; Andrea L.C. Schneider; Monisha A. Kumar (Resuscitation Plus)
Introduction: Neuroprognostication for disorders of consciousness, particularly after cardiac arrest, is critical. However rapidly evolving research has translated little to clinical practice, with neuroprognostication frequently deviating from evidence and clinical guidelines. We implemented a novel program that provides specialized, interdisciplinary, and longitudinal care to improve the practice of neuroprognostication. The objective of this study was to evaluate the impact of this program on provider attitudes and satisfaction towards neuroprognostication after cardiac arrest. Methods: We disseminated surveys across our health system to critical care providers and neurologists in the years before (2021, 2022) and after (2023) implementation of the program. The surveys assessed perceptions of, and satisfaction with, neuroprognostication after cardiac arrest. We used Fisher exact tests to compare program-exposed respondents to historical controls (2021 and 2022 respondents) and contemporary controls (2023 respondents without program exposure). Results: We received 545 responses from neurologists and critical care providers, including nurses, trainees, and attendings. Program-exposed respondents, relative to historical and contemporary controls respectively, reported greater usefulness of neuroprognostication (94% reporting often or always useful, versus 69% [p < 0.01]) and 68% [p < 0.01]), comprehensiveness of neuroprognostication (94% reporting often or always comprehensive, versus 76% [p = 0.02] and 66% [p < 0.01]), and greater satisfaction with neuroprognostication, particularly in comparison to the conventional model (63% reporting the program was “much better”). Conclusion: Implementation of a specialized neuroprognostication program was associated with largely favorable attitudes towards neuroprognostication among providers. These findings encourage further study of this paradigm, and consideration of broader adoption to improve the practice of neuroprognostication.